Keratin 36, a specific marker of tongue filiform papillae, is downregulated in squamous cell carcinoma of the mobile tongue - Brychtova, Veronika; Coates, Philip J; Hrabal, Vaclav; Boldrup, Linda; Fabian, Pavel; Vojtesek, Borivoj; Sgaramella, Nicola; Nylander, Karin (Molecular and clinical oncology, 2020)
Human keratin 36 (K36) is a member of the hair keratin family and is a marker of hair cortex differentiation. The human KRT36 gene is located on the long arm of chromosome 17 and belongs to the cluster of structurally unrelated acidic hair keratins. Recently, it has been reported that KRT36 mRNA is specifically expressed in normal tongue epithelium and downregulated in squamous cell carcinomas of the mobile tongue. Furthermore, KRT36 levels have been reported to be downregulated in clinically normal mobile tongue tissue that is adjacent to tumours, suggesting it could be a marker of pre-neoplastic changes. However, the exact role and the potential role of K36 in tongue tumour formation remains unclear. The aim of the present study was to investigate expression of K36 in a series of squamous cell carcinomas of the mobile tongue, normal mobile tongue and a small panel of other human tissues (normal tissue from the appendix, cervix, hair, lip, mamilla, nail, oesophagus, skin, thymus and vagina) and selected cancer tissue (cervical cancer, melanoma and basal cell carcinoma). Affinity purified polyclonal antibodies against K36 were generated and used for immunohistochemical analysis. The results revealed that in the normal tongue, K36 was detected specifically in the filiform papillae of the dorsal surface of the tongue. Additionally, none of the tongue cancer tissue samples were K36-positive. Immunostaining also revealed that K36 was expressed in nail beds, Hassal's corpuscles in the thymus and the hair cortex. However, K36 was not expressed in the squamous epithelia of the skin, cervix and oesophagus, and the squamous cells of cervical carcinomas, basal cell carcinoma or melanoma. The present data indicated that K36 may be inactivated in tumours of the tongue. However, whether this is part of the tumoural process or if it is an effect of the tumour itself remains to be elucidated.
Keywords: mobile tongue; squamous cell carcinoma; thymus; keratin 36; nail